Penerapan model problem based learning untuk meningkatkan sikap peduli lingkungan pada muatan pelajaran ipa peserta didik kelas iv sekolah dasar - Lilik Budi Maryanto; Hadi Mulyono; Sularmi Sularmi (Universitas Sebelas Maret, 2019)
The aim of this research was to increase the environmental attitude in science subject through implementation the used of Problem Based Learning in fourth grades of state primary school Musuk 1 Boyolali at 2018/2019 academic year. The research focus are teacher and student, totally 30 students. The kind of this research is a classroom action research was conducted in three cycles. The data was collected using techniques of debriefing, observation, questionnaire, also documentation. Data’s been validated with triangulation. Data analysis used in this study was technical analysis of Miles and Hubberman’s interactive analysis. The research showed an increased in environmental attitude. In pre-cycle, resulting in a percentage of 20% reaches the passing grade. The first cycle resulting in a percentage of 33% reaches the passing grade in classical terms, the second cycle resulting a percentage of 60% reaches the passing grade and the third cycle resulting in a percentage of 83% reaches the passing grade in classical terms. Based on these result, it could be concluded that the used of Problem Based Learning models increased environmental in fourth grades of state primary school Musuk 1 Boyolali at 2018/2019 academic year.